Fall Detection System for the Elderly People using the Earth’s Gravity: doi: 10.14456/mijet.2021.11 - Butsabong, Kiadtirat; Thephavongsa, Aphisith; Sa-Ngiamvibool, worawat (Engineering Access, 2021)
On population ageing, the major problems for elderly people are falls. These falls are the primary causes of injury, disability and accidental death. This article presents the development of the fall detection system for elderly people using the earth’s gravity. The proposed system uses a built-in accelerometer sensor of the smart phone to detect the older people falls and notify the administrator of the corresponding falls in real time. The earth’s gravity is used as a process of making choices by identifying a decision, gathering information, and assessing alternative resolutions. Samples of this research examination, obtained by a purposive sampling technique, were accounted from 30 sample examiners from both elderly and young persons with different weight. The experimental test-rig is a prototype application of fall detection on a smart phone. The statistical principles in terms of average and standard deviation were employed for the analysis. The evaluative results show that the proposed approach is desirable for the elderly people.